MO263KLOTHO IS PROTECTIVE IN THE CONTEXT OF ACUTE GLOMERULAR INJURY BUT IS NOT EXPRESSED IN PODOCYTES. (29th May 2021) - Charrin, Emmanuelle; Dabaghie, Dina; Mencke, Rik; Sen, Ilke; Möller-Hackbarth, Katja; Zambrano, Sonia; Olauson, Hannes; Patrakka, Jaakko
Abstract: Background and Aims: Podocyte integrity is crucial for the maintenance of glomerular function in health and disease. Numerous studies have reported that Klotho overexpression, or treatment with recombinant Klotho, reduces glomerular and tubular damage in mouse models of renal disease. However, the mechanism(s) of action are not fully understood. Several recent studies have also reported that Klotho is expressed in podocytes, where it protects against various types of injury. These findings conflict with previous studies, which have shown that renal Klotho expression is exclusively confined to proximal and distal tubular cells. Method: To address this discrepancy and enhance our understanding of the putative glomeruloprotective effects mediated by Klotho, we examined the expression pattern of Klotho in human and mouse kidney by several different methods, and explored its protective effects by overexpressing full-length human Klotho directly in podocytes or in a distant organ (i.e. liver). Results: Data at the mRNA and protein levels all converged towards an absence or very low expression of Klotho in podocytes. The generation of a podocyte-specific Klotho knockout mouse further demonstrated that its deletion did not affect glomerular structure or function. Moreover, Klotho deficiency did not worsen glomerular injury in an experimental model of glomerulonephritis (anti-GBM). However, when Klotho was overexpressed in hepatocytes (Alb-cre;hKlotho fl/+ - Alb-hKL), serum Klotho increased drastically with no changes in Fgf23 or phosphate metabolism. In mice challenged with anti-GBM, renal histology and ultrastructure of the filtration barrier was less severely affected in Alb-hKL compared to WT mice. There were also significantly less albuminuria, podocyte loss and interstitial fibrosis in Alb-hKL mice compared to their WT littermates. In contrast, mice which overexpressed Klotho in podocytes (Pod-hKL) were not protected from renal injury. Conclusion: Taken together, these results strongly suggest that Klotho is not expressed in any substantial amounts in human or mouse podocytes, and that membrane-bound Klotho does not play a role in podocyte biology. Importantly, our results confirm a beneficial role for soluble Klotho in protecting podocytes against injury, and in maintaining glomerular integrity and function.